Inmates’ Perceptions of the Effectiveness of Technical and Vocational Training (TVET) and Entrepreneurship Training Program - Abdullah, Nurul Hidayah Liew; Mat Husin, Siti Nurani; Paimin, Aini Nazura; Mohamed, Maziana; Mahat, Hanifah (Journal of Technical Education and Training, 2021)
: Issues on crime and unemployment among ex-inmates contribute to recidivism in the country even though they were given technical and vocational (TVET) and entrepreneurship trainings by the prison authority. Therefore, the purpose of this study was to identify the perception of inmates in prison on the effectiveness of TVET and entrepreneurship training. The design of the study used in this study was a method of review with a quantitative approach. Data was collected using a set of questionnaires and analyzed using statistical package software for the Social Science (SPSS version 23.0). A total of 222 respondents, inmates who have undergone and are undergoing TVET were involved in the study. The reliability of instruments was at an excellent and effective level with the consistency level of 0.871 and 0.915. Data analysis was done in the form of frequency, percentage, mean, standard deviation and Pearson correlation test (r). The findings of the study showed that perception of the effectiveness of TVET and entrepreneurship skills in prison was high which were the mean value of 4.18 and 4.28 respectively. In addition, the findings showed that there was a significant relationship between TVET effectiveness and entrepreneurship skills among the respondents, r=0.557 (P â‰¤ 0.01). In conclusion, the inmates perceived that TVET and entrepreneurship skills taught in prison are beneficial. Apart from that, it could provide added value in their continuity of survival once released primarily in the field of employment and entrepreneurship activities.